Inhibiting surface and subsurface damage in ultrasonic vibration-assisted ultraprecision diamond cutting of high-entropy alloy - Yintian Xing; Yue Liu; Yuhan Li; Tengfei Yin; Denghui Li; Changxi Xue; Wai Sze Yip; Suet To (Journal of Materials Research and Technology)
High-entropy alloys (HEAs) are a potential industrial material for large-scale applications because of their superior physical and chemical attributes. However, owing to the incomplete understanding of the manufacturing mechanism for this material, it is a challenge to realize ultra-precision nanoscale manufacturing of HEAs while preventing surface and subsurface damage. Therefore, in this work, ultrasonic vibration-assisted diamond cutting (UVDC) was utilized to manufacture HEAs workpieces, with the aim of clarifying and revealing the formation mechanisms of high-precision surface integrity. The scientific phenomena of material removal characteristics are explored and investigated, encompassing a range from macroscopic surface overall topography to microscopic subsurface atomic changes. This is achieved through comprehensive comparisons of the workpiece surface, subsurface features, chip morphology, and tool damage in cutting processes with and without high-frequency ultrasonic vibration assistance. Results indicate that the diverse machinability advantages of HEAs in intermittent cutting can effectively inhibit surface and subsurface damage, including better cutting stability, smoother material removal, and lower tool wear. This study enhances the understanding of the high-precision surface formation mechanisms in HEAs by suppressing damage during UVDC, thereby meeting the stringent demands of practical applications.